The Graeco-Bactrian and Indo-Greek World (Taylor & Francis, 2021)
This volume provides a thorough conspectus of the field of Graeco-Bactrian and Indo-Greek studies, mixing theoretical and historical surveys with critical and thought-provoking case studies in archaeology, history, literature and art. The chapters from this international group of experts showcase innovative methodologies, such as archaeological GIS, as well as providing accessible explanations of specialist techniques such as die studies of coins, and important theoretical perspectives, including postcolonial approaches to the Greeks in India. Chapters cover the region's archaeology, written and numismatic sources, and a history of scholarship of the subject, as well as culture, identity and interactions with neighbouring empires, including India and China. The Graeco-Bactrian and Indo-Greek World is the go-to reference work on the field, and fulfils a serious need for an accessible, but also thorough and critically-informed, volume on the Graeco-Bactrian and Indo-Greek kingdoms. It provides an invaluable resource for anyone interested in the Hellenistic East.
English
Keywords: Ancient history; Collecting coins, banknotes, medals and other related items; Ethnic studies; Bactrian, Graeco, Greek, Indo, World